Performance and analysis of kappa-carrageenan hydrogel for PFOA-contaminated soil remediation wastewater treatment - Alsaka, Lilyan (2024)
Perfluorooctanoic acid is an emerging pollutant with exceptional resistance to degradation and detrimental environmental and health impacts. Conventional physical and chemical processes for Perfluorooctanoic acid are either expensive or inefficient. This study developed an environmentally sustainable and cost-effective gravity-driven kappa-carrageenan (kC)-based hydrogel for perfluorooctanoic acid (PFOA) removal from synthetic and actual wastewater. Two kC filters were prepared by mixing activated carbon (AC) or vanillin (V) with the kC hydrogel to optimize the hydrogel selectivity and water permeability. Experimental work revealed that the PFOA rejection and water permeability increased with the AC and V concentrations in the kC hydrogel. Experiments also evaluated the impact of feed pH, PFOA concentration, hydrogel composition, and hydrogel thickness on its performance. Due to pore size shrinkage, the AC-kC and V-kC hydrogels achieved the highest PFOA rejection at pH 4, whereas the water flux decreased. Increasing the PFOA concentration reduced water flux and increased PFOA rejection. For 2 cm hydrogel thickness, the water flux of 3%kC-0.3%AC and 3%kC-3%V hydrogels was 25.6 LMH and 21.5 LMH, and the corresponding PFOA rejection was 86.9% for 3%kC-0.3%AC and 85.7% for 3%kC-3%V. Finally, the kC-0.3%AC hydrogel removed 81.1% of PFOA from wastewater of 179 mg/L initial concentration compared to 79.3% for the kC-3%V hydrogel. After three filtration cycles, the water flux decline of 3%kC-0.3%AC was less than 10%. The gravity dead-end kC hydrogel provides sustainable PFOA wastewater treatment with biodegradable and natural materials.